Optimalisasi Sosial Media Sebagai Sarana Promosi Usaha Kecil Menengah Meningkatkan Penjualan di Masa Pandemi Covid-19 - Endah Fantini; Mohammad Sofyan; Ade Suryana (CV ODIS, 2021)
This research aims to know the development and role of social media as an effort to market online businesses, business motivation to increase sales during the Covad-19 pandemic. Optimization of social media as a business strategy of SMEs, constraints of SMEs in optimizing social media for online businesses. The method used is descriptive qualitative with literature study. Based on the results of the study shows that internet use during the covid-19 pandemic is increasing rapidly, 3 social media are often visited, namely Facebook, Instagram, and youtube. In online marketing, social media has several important roles including effective branding and promotion. Factors that motivate SMEs to start a business include economic success drive, confidence in self-capability, self-esteem, social responsibility, freedom to manage a business, fondness for the work pursued; and, and role model. Optimization of social media as an SME business strategy, among others, is consistently doing business every day to increase sales. While the obstacles faced by SMEs in optimizing social media for online businesses are cost-leadership, differentiation, and focus. This research aims to know the development and role of social media as an effort to market online businesses, business motivation to increase sales during the Covad-19 pandemic. Optimization of social media as a business strategy of SMEs, constraints of SMEs in optimizing social media for online businesses. The method used is descriptive qualitative with literature study. Based on the results of the study shows that internet use during the covid-19 pandemic is increasing rapidly, 3 social media are often visited, namely Facebook, Instagram, and youtube. In online marketing, social media has several important roles including effective branding and promotion. Factors that motivate SMEs to start a business include economic success drive, confidence in self-capability, self-esteem, social responsibility, freedom to manage a business, fondness for the work pursued; and, and role model. Optimization of social media as an SME business strategy, among others, is consistently doing business every day to increase sales. While the obstacles faced by SMEs in optimizing social media for online businesses are cost-leadership, differentiation, and focus.